Drafting basics - Fullmer, Donna Lynne, ....- (New York : Fairchild, 2012)
Drafting Basics offers an introduction to the art of hand drafting using lead and ink. Students will first learn how to communicate through fundamental two-dimensional drawings including lettering, plans, elevations, and sections. The book then covers the basics of technical drafting, reinforcing the importance of the hand skills required of interior design professionals at every point along the career path.
Includes index.
Keywords: Drawing -- Technique; Architectural drawing -- Handbooks, manuals, etc; Architectuur ; tekenen